Modigliani’s comments on Sylos Labini’s theory of unemployment (1956-1958) - Antonella Rancan (PSL Quarterly Review, 2014)
This note discusses Modigliani’s and Sylos Labini’s unemployment theory starting from a long letter Modigliani wrote to his friend and colleague, commenting the provisional edition of “Oligopolio e Progresso Tecnico” (1956). While in his influential article review (1958) Modigliani especially analysed and developed along original lines Sylos Labini’s microeconomic theory, in the letter he deeply discussed Sylos Labini macroeconomics. Modigliani criticized Sylos Labini’s classical definition of investment and the ensuing confusion between monetary and real causes of unemployment. From their correspondence their different theoretical perspective clearly stands out: Modigliani was interested in explaining the emergence of unemployment equilibrium in a static context, Sylos Labini its persistence as the result of structural changes.